Can artificial intelligence help identify elder abuse and neglect?. Issue 1 (1st January 2020) - Rosen, Tony; Zhang, Yiye; Bao, Yuhua; Clark, Sunday; Elman, Alyssa; Wen, Katherine; Jeng, Philip; Lachs, Mark S.
ABSTRACT: A health care encounter is a potentially critical opportunity to detect elder abuse and initiate intervention. Unfortunately, health care providers currently very seldom identify elder abuse. Through development of advanced data analytics techniques such as machine learning, artificial intelligence has the potential to dramatically improve elder abuse identification in health care settings.